2019
DOI: 10.1177/1048291119867740
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety for Migrant Domestic Workers in Canada: Dimensions of (Im)mobility

Abstract: This study examines the occupational health and safety experiences of migrant workers employed as live-in caregivers in Fort McMurray, Alberta, Canada. Interviews with and surveys of caregivers identify four categories of common occupational hazards, including fatigue, psychosocial stress, physical hazards, and exposure to harassment and abuse. These hazards are systemically perpetuated, made invisible and rendered irremediable by intertwined (im)mobilities. At the macro-level, they include highly circumscribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…In this study, working for more than 8 hours per day was associated with a high likelihood of experiencing work-related injuries. This study is in line with the study that reported long daily hours of work, which give rise to fatigue, increased the risk of work-related injuries [17,24,34,45]. The possible reason for this might be long working hours may lead to fatigue, physical and mental stress which can possibly cause weariness, sleepiness, irritability, reduced alertness and impair judgment/decision making that increase the risk of physical injuries and susceptibility to accidents [46].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, working for more than 8 hours per day was associated with a high likelihood of experiencing work-related injuries. This study is in line with the study that reported long daily hours of work, which give rise to fatigue, increased the risk of work-related injuries [17,24,34,45]. The possible reason for this might be long working hours may lead to fatigue, physical and mental stress which can possibly cause weariness, sleepiness, irritability, reduced alertness and impair judgment/decision making that increase the risk of physical injuries and susceptibility to accidents [46].…”
Section: Discussionsupporting
confidence: 89%
“…However, underreporting of medical conditions is significant due to limited access to health services, and fear of lost wages or jobs [23]. The occupational health and safety (OHS) of these migrant workers remains a fraught and neglected issue [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a classic legal analysis of regulatory frameworks and administrative tribunal decisions in seven Canadian jurisdictions, combined with information provided from interviews with key informants, we found that the invisibility of the internally (within country) mobile workforce, as well as the alternating visibility and invisibility of the temporary foreign workforce, contribute to reduced effectiveness of the OHS and WC regulatory frameworks, a finding also identified by Cedillo et al 4 and Hill et al 5 As we shall see, the OHS regulatory challenges vary and can be complex depending on the nature of employment, on time and distance considerations, as well as on the worker's status and particular circumstances (gender, language proficiency, nature of migration) which can increase their vulnerability. Challenges for effective application of WC legislation also exist, although their sources are different.…”
Section: Introductionsupporting
confidence: 53%
“…Although much research has examined the occupational health and safety (OHS) and social security implications of nonstandard or precarious employment (i.e., temporary, part-time, and triangular employment relationships), 2,3 and to a lesser extent OHS experiences and challenges of temporary foreign workers, [4][5][6] the relationship between E-RGM and nonstandard employment is understudied, as are the implications of E-RGM associated with standard employment for regulatory effectiveness of OHS and social protections such as workers' compensation (WC). Further complicating our understanding of these dynamics is the lack of systematic collection of national statistics in relation to all forms of E-RGM; statistics specific to each province and territory are not always available.…”
Section: Introductionmentioning
confidence: 99%
“…He discusses what the team and partners learned through the program about the particular work and life context and related needs of new-to-Alberta workers that created challenges and prompted program changes throughout the three-year period. The team's learnings echo what Hill et al 3 found in their study of OHS for domestic workers including, for example, the vulnerability of workers whose contract ties them to a specific employer, who are socially and geographically isolated, may speak little to no English, and who can be profoundly affected by changes to Canada's various foreign worker programs. Jared also considers the conditions and supports required to meaningfully help new-to-Alberta workers.…”
Section: Introductionmentioning
confidence: 57%